Pictorial Personality Traits Questionnaire for Children (PPTQ-C)—A New Measure of Children's Personality Traits - Maćkiewicz, Marta; Cieciuch, Jan (Frontiers in Psychology, 2016)
In order to adjust personality measurements to children’s developmental level, we constructed the Pictorial Personality Traits Questionnaire for Children (PPTQ-C). To validate the measure, we conducted a study with a total group of 1028 children aged between 7 and 13 years old. Structural validity was established through Exploratory Structural Equation Model. Criterion validity was confirmed with a multitrait-multimethod analysis for which we introduced the children’s self-assessment scores from the Big Five Questionnaire for Children. Despite some problems with reliability, one can conclude that the PPTQ-C can be a valid instrument for measuring personality traits, particularly in a group of young children (aged approximately 7 to 10 years).